Prenatal Diagnosis of Chromosome 22q11.21 Microduplication Syndrome in a Fetus with Congenital Malformation of the Cardiovascular System: Case Report - Vira O. Galagan; Yuliia V. Dudierina; Anna O. Pavlova (Ukrainian Journal of Cardiovascular Surgery, 2022)
A clinical case of microduplication of chromosome 22q11.21 in a fetus with a malformation of the cardiovascular system (vascular ring) is presented. This anatomical variant of the vascular ring is extremely rare and is formed by the pathological circumflex retroesophageal left-sided cervical aortic arch with the left arterial ductus arteriosus. The anatomical features of the circumflex cervical aortic arch are the left-sided pathological curved aortic arch in combination with the right-sided descending aorta. This vascular pathology can cause compression of the trachea and esophagus. This variant of the vascular ring is extremely unfavorable for surgical correction. Chromosome 22q11.21 microduplication syndrome is associated with the clinical presentation of “cat eye syndrome”. The clinical case description shows unique data from instrumental and genetic studies. All stages of examination of a pregnant woman from primary to tertiary medical care are described. The features and importance of a multidisciplinary approach are also presented.Every case of congenital heart defect in fetus, confirmed by echocardiographic method in a specialized institution, requires medical and genetic counseling. Using of the highly sensitive specific molecular cytogenetic method, comparative genomic hybridization, in prenatal diagnosis allows for timely diagnosis of microstructural disorders of chromosomes in fetus. Follow-up of a pregnant woman with congenital heart defect in the fetus requires a multidisciplinary approach not only to improve diagnosis and treatment, but also to calculate genetic risk.